Associations between activity-related behaviours and standardized BMI among Australian adolescents. - Allender, S; Kremer, P; de Silva-Sanigorski, A; Lacy, K; Millar, L; Mathews, L; Malakellis, M; Swinburn, B (2011)
OBJECTIVES: To examine the relationships between physical activity, sedentary behaviour and body mass index (BMI) among a sample of Australian adolescents. METHODS: Anthropometric, demographic and behavioural data were collected from students (n=3040 mean age 14.6, 44% female) from 12 secondary schools in South West Victoria, Australia (response rate=48.6%). The appropriate descriptive, univariate and regression analysis were used to examine the strength of the associations between physical activity, sedentary behaviour and odds of overweight or obese and the effect of interaction between physical activity and sedentary behaviour on odds of overweight and obese. RESULTS: Males were more likely to be active during the school day than females and had higher median hours of screen time per school day. Physical activity during the school day was associated with higher standardized BMI (BMI-z) among males. Higher levels of activity after school were associated with lower BMI-z for males and females. For both males and females the odds of overweight or obese were higher among the least active. An interaction was observed for females whereby the prevalence of overweight and obesity among the most physically active was lowest for the least sedentary and highest for the most sedentary. CONCLUSIONS: The relationships between physical activity, sedentary behaviour and BMI-z were complex. Interventions to reduce BMI through increasing physical activity or decreasing sedentary behaviour need to consider the complex inter-relationships between these variables and moderating factors such as age, sex and socio economic status in their design and interpretation.